2019
DOI: 10.1108/intr-03-2018-0103
|View full text |Cite
|
Sign up to set email alerts
|

Does more crowd participation bring more value to crowdfunding projects? The perspective of crowd capital

Abstract: Purpose The purpose of this paper is to focus on investigating the impact of crowd participation on degree of project success, which is defined as the total amount of funds a project can obtain after it reaches its initial funding goal threshold. Design/methodology/approach Drawing on the theory of crowd capital, this study develops six hypotheses about the impact of crowd capability of a fundraiser (i.e. project updates, goal setting, reward levels and social media usage) and crowd participation (i.e. namel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 52 publications
6
29
0
Order By: Relevance
“…Examinations of rewards on crowdfunding platforms have been lacking from the literature, with one study stating ‘the most distinctive feature of reward‐based crowdfunding – rewards – has seldom been studied’ (Simons et al, 2017, p. 4346). To date, research on crowdfunding rewards has emphasised basic characteristics of rewards offered in reward portfolios, such as the number of rewards or limited availability rewards (eg, Kunz et al, 2017; Lin et al, 2016; Yin et al, 2019; Zhang & Chen, 2019). Our study extends this research through an in‐depth examination of the content of the rewards project campaigns offer and the effects of the reward portfolio design on funding success.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Examinations of rewards on crowdfunding platforms have been lacking from the literature, with one study stating ‘the most distinctive feature of reward‐based crowdfunding – rewards – has seldom been studied’ (Simons et al, 2017, p. 4346). To date, research on crowdfunding rewards has emphasised basic characteristics of rewards offered in reward portfolios, such as the number of rewards or limited availability rewards (eg, Kunz et al, 2017; Lin et al, 2016; Yin et al, 2019; Zhang & Chen, 2019). Our study extends this research through an in‐depth examination of the content of the rewards project campaigns offer and the effects of the reward portfolio design on funding success.…”
Section: Discussionmentioning
confidence: 99%
“…Research has also indicated a downside to offering too many rewards; that is, the more rewards offered the lower the chances of successful funding outcomes (Chen et al, 2016;Xiao et al, 2014). However, findings regarding the number of rewards offered have been inconsistent because offering more rewards has also been demonstrated to increase the chances of funding success (Kunz et al, 2017;Lin et al, 2016;Yin et al, 2019). Researchers have also discovered that limiting the number of a particular reward offered and adding rewards later in the funding period can increase funding success (Lin et al, 2016).…”
Section: Review Of Crowdfunding Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…First, most of the related empirical studies have only focused on one or two dimensions of information description. Some have only examined the effect of information quantity [22,27,29,30,33,34], some have only concerned information quality [35][36][37], and some have only studied information attitude [38,39]. Second, although few researchers have considered all the three dimensions of information description as antecedents of crowdfunding success, they have only focused on one or two aspects of each dimension of information description.…”
Section: Introductionmentioning
confidence: 99%
“…As soon as individuals consider the decisions of other individuals as more informative than their own information, it is likely that they will ignore their information and imitate the actions of other individuals in order to overcome current uncertainty (Sun 2013). This cascade is increasing, and a possible immediate successor will perceive even more reasons to ignore the own information (Yin 2019). Previous IS research showed that, due to large amounts of information available about the purchase decisions of consumers online, the Internet is the ideal environment for this type of herd behavior.…”
Section: Hypotheses Developmentmentioning
confidence: 99%